A specimen of the internal control system on the stock in light of the application JIT system In construction companies - الحمداني, بهاء حسين; حمادي, يحيى علي (Journal of Economics and Administrative Sciences, 2015)
Suffer most of the facilities of the high cost of inventory , which affects the high cost of the product and thus affects many administrative decisions , as well as suffer the facilities of the systems developed by the provisions of inventory control , and this problem is exacerbated in the construction sector where the inventory in the form of Construction spin of the Year for another it becomes difficult to control the cost effectively , and is the research problem in question follows: What are the implications of the use of the system in time inventory accounting system for the contracting company does kills Alrkaah to the provisions of the cost of inventory and what is the optimal approach to inventory control ? Find assumed that the presence of an efficient system of internal control and effective inventory and using modern cost techniques leads to: Provide useful information to verify the adequacy and effectiveness of the use and Established to protect stock from misuse and rationalize its use. The most important conclusions of her research show that the use of backflash costing will claim to control provisions mandated inventory better, and because it carries the cost of stocks last term cost of materials only without Pfih cost elements which facilitates the process of the provisions of censorship by comparing the stock material with production under operating with the cost of materials disbursed